The Home Edit Life : a guide to organizing absolutely everything - Shearer, Clea, 1982-; Teplin, Joanna, 1979- (New York : Clarkson Potter/Publishers, 2020)
"The New York Times bestselling authors of The Home Edit show you how to contain the chaos and organize every aspect of your life, including hobbies and activities, work and office spaces, luggage and travel, and so much more"--.
Includes index.
Keywords: Storage in the home; Orderliness